Immune checkpoint modulators in cancer immunotherapy: Recent advances and combination rationales - Fan, Li; Li, Yue; Chen, Jia-Yu; Zheng, Yong-Fa; Xu, Xi-Ming (Cancer letters, 2019)
As a new hallmark of cancer, immune surveillance evading plays a critical role in carcinogenesis. Through modulating the immune checkpoints, immune cells in tumor microenvironment can be harnessed to battle cancer cells. In recent years, the administration of anti-CTLA or/and anti-PD-1/L1 antibody has exhibited unexpected antitumor effect in multiple types of cancer, motivating the researchers to find more potential immune checkpoints as clinical targets. A wealth of clinical trials have been done to evaluate the safety and efficacy of monotherapy or combination therapy with immune checkpoint modulators. However, there still exist problems such as low response rate and adverse events in the clinical, which in turn leads us to the basic study. The better understanding of the crosstalk between the immune cells and the cancer cells within the microenvironment may inspire us new ideas for cancer treatment. In this review, we mainly summarize the recent advances in application of immune checkpoint modulators and the combination rationales, and discuss the problems existing in the precision therapy with immune checkpoint modulators. •The application of anti-PD and anti-CTLA immune checkpoint modulators alone or in combination has exhibited unexpected antitumor effect in multiple types of cancer.•There are a lot of clinical studies of other checkpoint modulators, including the inhibitory modulators (LAG-3 inhibitor) and stimulatory modulators (agonists of CD27, OX-40, CD40, ICOS, 4-1BB and GITR), but their efficacy is still pending.•Despite the rapid progress in cancer immunotherapy, there still exist some problems to achieve precision therapy with immune checkpoint modulators.